Evaluasi Kesesuaian Lahan Beberapa Komoditas Tanaman Hortikultura dan Perkebunan di Kawasan Agrowisata Desa Kerta Kecamatan Payangan Kabupaten Gianyar - ADELIA, REZA; DIBIA, I NYOMAN; MEGA, I MADE (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2016)
Land Suitability Evaluation of Horticultureand Plantation Commodities in the Kerta’s Village Payangan Subdistrict Gianyar District Judging from their natural conditions Kerta’s Village Payangan Subdistrictpotential in developing horticultural crops (pineapple, banana, orange, and bark,) and plantations (robusta coffee). The purpose of this study are (1) determine the suitability of land several commodities (pineapple, banana, orange, and bark) and plantations (robusta coffee), (2) determine the limiting factor horticultural commodities (pineapple, banana, oranges, and bark) and plantations ( robusta coffee), (3) create a map of the land suitability of horticultural commodities (pineapple, bananas, oranges, and bark) and plantations (robusta coffee). This study uses a survey of the land suitability evaluation by Djaenudin and others (2003). Based on the results of delineation, there are 6 units of homogeneous land. Actual Land Suitability horticultural crops (pineapple, banana, orange, and bark,) ranged from S2, S3 and N while the suitability of potential land to plant pineapples, oranges, and the bark is on land units IVHPKC, VHPKC, IVHPTG, VHPTG is S1 and to plant banana on land is S2. On land units VIHPKC and VIHPTG for banana plants belonging to N by a factor limiting the slopes. For Robusta coffee classified as S1 on all land units except on land VIHPKC and VIHPTG.
Keywords: land suitability; land evaluation; land quality/land characteristic and limiting factor